Flipped Classrooms for Introductory Computer Programming Courses - Sobral, Sónia Rolland (2021)
Teaching and learning how to program are not easy tasks. Disapproval and dropout rates are a concern for everyone concerned with the topic. Therefore, it is necessary to look for strategies that improve the motivation of students who start a programming course, also improving success rates and decreasing dropout rates. The inverted class model, or flipped classroom, has been used in several experiments, showing very good results. The objectives of this teaching-learning technique is to change the traditional order: students have contact with new subjects before the classroom, using videos, texts or other material, as well as small online tests to check their knowledge. In this way, the face-to-face classes are reserved for discussion, doubts and application of previously acquired knowledge. The purpose of this paper is to analyze the scientific production on Flipped classrooms in introductory programming courses indexed in Elsevier’s Scopus. The sample is composed by 45 articles in total. The results obtained by bibliometric analysis showed when and where those documents are published, who are the authors and what is the focus of said articles. We also analyzed the most cited documents. We made a summary of the articles, namely in what refers to the sample size of the experiences, which programming language is used, in which universities the articles are made, which technology is used, as well as which methods are used in order to create inverted classes and which are the objectives and results of these experiences reported on the articles.. We managed to get a global view of the theme, getting a strong analysis for those who want to use flipped classrooms for teaching programming.